2013
DOI: 10.1166/jnn.2013.6871
|View full text |Cite
|
Sign up to set email alerts
|

Prussian Blue Modified Ferritin as Peroxidase Mimetics and Its Applications in Biological Detection

Abstract: Ferritins are natural nanoscale structures composed with 24 subunits endowed with similar three-dimensional structures. The iron is stored in the form of ferrihydrite phosphate in the hollow spherical ferritin shells. Prussian blue nanoparticles (PBNPs) have been certified a kind of mimetic enzyme with the advantages of stability, high catalytic activity and low prices. In this context, we designed a strategy to synthesize PBNPs of small size using ferritin as template and meanwhile retain the biological prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
1
27
0
3
Order By: Relevance
“…Numerous papers (see Table 6) described the ability of PBA-NZ to react with typical ROS-enzyme substrates, such as TMB, ABTS and NADH [169]. PB and PBAs are used successfully in optical biosensors as a result of their PO-like properties [12,16,[169][170][171][172][173][174][175]. The first communications concerning electrochemical reduction of H 2 O 2 on PB-modified glassy carbon electrode were done by Itaya and colleagues [164,165].…”
Section: Nanozymes As Peroxidase Mimeticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous papers (see Table 6) described the ability of PBA-NZ to react with typical ROS-enzyme substrates, such as TMB, ABTS and NADH [169]. PB and PBAs are used successfully in optical biosensors as a result of their PO-like properties [12,16,[169][170][171][172][173][174][175]. The first communications concerning electrochemical reduction of H 2 O 2 on PB-modified glassy carbon electrode were done by Itaya and colleagues [164,165].…”
Section: Nanozymes As Peroxidase Mimeticsmentioning
confidence: 99%
“…In 2000, this group named PB an "artificial PO" [177]. At the same time, a large number of other scientific groups, especially from China, worked hard on this problem [148,154,[156][157][158][159]166,[168][169][170][171][172][173][174].…”
Section: Nanozymes As Peroxidase Mimeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al reported the synthesis of a nanosized PB‐encapsulated structure using FRT as the reactor where ferrocyanide and ferric ion are mixed together. [ 32 ] While they developed this material as a mimetic peroxidase for glucose detection, the special structure of PB‐encapsulated FRT should also have the capacity of using photothermal conversion for PTT.…”
Section: Proteins As Carriers Of Drugs/photosensitizersmentioning
confidence: 99%
“…There have been some reports that naturally occurring ferritin is equivalent to a storage compartment for iron in animal and plant cells [115]. Zhang et al [116] devised a strategy to use ferritin as a template for the synthesis of small, Prussian blue-modified ferritin nanoparticles (PB-Ft NPs), which retain the biological characteristics of ferritin. Their results showed that the PB-Ft NPs have a mean size of 22.8 nm, and retain specificity and peroxidase-like activity.…”
Section: Magnetic Nanoparticles Themselves As a Drug Delivery Systemmentioning
confidence: 99%